2012
DOI: 10.1310/tsr1905-377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intensive Rehabilitation on Physical Function and Arterial Function in Community-Dwelling Chronic Stroke Survivors

Abstract: These findings suggested that intensive rehabilitation for stroke patients during the chronic stage preserved physical function and improved arterial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 16 publications
2
30
0
3
Order By: Relevance
“…The majority of studies (13/15, 86.6%) had a score of moderate quality (5,6,8,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) and the other with lower quality (2/15, 13.4%) (27,28) (5,6,17,18,(20)(21)(22)(24)(25)(26)(27)(28) "the number of test repetitions stand-up / sit down on chair in 30 seconds "(1/15, 6.7%) (23) and "test number of repetitions stand-up / sit down on chair 60 seconds "(1/15, 6.7%) (19) ( Table 2). The tests were used to refer to functionality, (22,27) muscle strength in lower limb (17,25) performance from sitting to standing (19) and balance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of studies (13/15, 86.6%) had a score of moderate quality (5,6,8,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) and the other with lower quality (2/15, 13.4%) (27,28) (5,6,17,18,(20)(21)(22)(24)(25)(26)(27)(28) "the number of test repetitions stand-up / sit down on chair in 30 seconds "(1/15, 6.7%) (23) and "test number of repetitions stand-up / sit down on chair 60 seconds "(1/15, 6.7%) (19) ( Table 2). The tests were used to refer to functionality, (22,27) muscle strength in lower limb (17,25) performance from sitting to standing (19) and balance.…”
Section: Resultsmentioning
confidence: 99%
“…The tests were used to refer to functionality, (22,27) muscle strength in lower limb (17,25) performance from sitting to standing (19) and balance. (6) Most studies (10/15, 80%) (5,6,(17)(18)(19)(21)(22)(23)(24)27) utilized sample size greater than 12 individuals, independent ambulating for 10 meters with or without assistive device and mean age between 42 to 59.5 years (5,6,17,18,20,25,26) or 60 to 81.2 years. (8,19,(21)(22)(23)(24)27,28) Approximately 93.3% of studies (14/15) described the injury time of the individuals assessed, given as greater than 11 months (5,6,8,17,18,(20)(21)(22)(23)(24)(25)(26)(27)(28) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…49 Only one study has examined the effects of exercise on arterial function in individuals with stroke. Takatori et al 50 concluded that intensive strengthening may have some benefit to vascular stiffness on the paretic side, but analogous findings were not observed on the nonparetic side.…”
Section: Discussionmentioning
confidence: 99%